Fracture initiation pressure prediction of hydraulic fracturing for layered reservoirs considering borehole deformation - Wang, Yingwei; Wang, Man; Niu, Zehua; Chen, Zhaofan; Min, Rui; Zheng, Jingwei (Frontiers in Earth Science, 2024)
Accurately predicting fracture initiation pressure (FIP) is crucial for successfully applying hydraulic fracturing technology in layered reservoirs. However, existing models overlook the effects of rock anisotropy and borehole deformation. In this study, we simplified the layered reservoir to a transversely isotropic medium and developed a model to estimate borehole deformation precisely. Based on this estimated deformation, we created a model to predict fracture initiation pressure in hydraulic fracturing. By comparing previous models and experimental data, we validated the effectiveness of these proposed models. We examined the impacts of various factors on borehole deformation, fracture initiation pressure, and initiation angle. The results revealed that circular boreholes in layered reservoirs deform into elliptical boreholes under in situ stress, with the major axis not aligning with the principal stress direction, which highlights the significant impact of rock anisotropy on borehole deformation. Furthermore, the fracture initiation pressure of hydraulic fracturing either increases or decreases following borehole deformation, depending on specific geological parameters. The calculated initiation angle after borehole deformation is within 10°, closer to previous experimental results, underscoring the notable effect of borehole deformation on hydraulic fracturing.